Rock Mass Discontinuity Characterisation Using Image Analysis - Ahmadi, Asma' (Universiti Sains Malaysia, 2021)
Measuring spatial attitude (dip and dip direction) of rock mass discontinuities is usually done by hand with a compass/clinometer via scanline survey, which takes time and involves some censoring. For rock slope practitioners, digital photogrammetry has evolved into a helpful remote characterisation technique, especially in circumstances where physical discontinuity measuring is difficult or risky. In this study, models are designed, and 3D printed as to create a control environment which represent the actual rock mass discontinuity commonly found at site. Data acquisition is obtained by using a smartphone, Apple iPhone 12 Pro and an Unmanned Aerial Vehicle (UAV), DJI Phantom 4 Pro mounted with 20 megapixels camera to collect multiple overlapping images. For 3D analysis, these images are transformed into dense point cloud data using Metashape software and later computed in CloudCompare to obtain the orientation results in terms of dip and dip direction by utilising its FACET plugin. Meanwhile, one single image of the surface of the model is computed in the Working Face software to compute for the 2D analysis. Comparison between the two analyses show the capabilities and limitations of each of the softwares used in this research in detecting the nature of discontinuities.